2020
DOI: 10.1007/s00248-020-01487-9
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Surface Glycan Biosynthesis, Composition, Inhibition, and Function in Cnidarian-Dinoflagellate Symbiosis

Abstract: The success of symbioses between cnidarian hosts (e.g. corals and sea anemones) and microalgal symbionts hinges on the molecular interactions that govern the establishment and maintenance of intracellular mutualisms. As a fundamental component of innate immunity, glycan-lectin interactions impact the onset of marine endosymbioses, but our understanding of the effects of cell surface glycome composition on symbiosis establishment remains limited. In this study, we examined the canonical N-glycan biosynthesis pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“… 29 32 ). Work in these systems has uncovered key mechanisms for control of symbiont densities 33 35 , lectin and other proteins involved in symbiont recognition and endocytosis 36 , 37 , as well as differences in the repression of the host immune system by symbionts of different genera 38 . Still, much can be learned from studying adult calcifying corals in a naturally aposymbiotic state.…”
Section: Introductionmentioning
confidence: 99%
“… 29 32 ). Work in these systems has uncovered key mechanisms for control of symbiont densities 33 35 , lectin and other proteins involved in symbiont recognition and endocytosis 36 , 37 , as well as differences in the repression of the host immune system by symbionts of different genera 38 . Still, much can be learned from studying adult calcifying corals in a naturally aposymbiotic state.…”
Section: Introductionmentioning
confidence: 99%
“…Several specific glycan moieties have been characterized in Symbiodiniaceae. High-mannoside glycans are the most abundant type of N-glycan in B. minutum , but increasing the abundance of high-mannoside glycans with inhibitors for glycan maturation pathways can decrease the colonization capacity of B. minutum ( 12 ). Similarly, Tortorelli et al ( 13 ) found higher abundances of high-mannoside glycans as measured by lectin array in nonnative species of algae, Cladocopium goreaui , and Fugacium kawagutii , compared to B. minutum , suggesting that an overabundance of high-mannoside glycans can inhibit symbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Tortorelli et al ( 13 ) found higher abundances of high-mannoside glycans as measured by lectin array in nonnative species of algae, Cladocopium goreaui , and Fugacium kawagutii , compared to B. minutum , suggesting that an overabundance of high-mannoside glycans can inhibit symbiosis. The second-most abundant group of N-glycans in B. minutum are galactosylated glycans ( 12 ). These glycans are less abundant in nonnative species of algae, Symbiodinium pilosum , C. goreaui , and F. kawagutii , as measured by lectin array compared to B. minutum ( 11 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations